Ecuador: analysis of the global competitiveness report for the 2016-2019 period - Jiménez Cabrera, Jackson (2022)
At a global level, one of the most recognized reports on the competitiveness of nations is theGlobal Competitiveness Report (RGC), and its main indicator the Global Competitiveness Index(GCI) developed and published annually by the World Economic Forum (WEF, or WEF by itsacronym in English). During the period 2016 to 2019 Ecuador has presented various levels ofpositioning of its index in the RGC, placing it with deficient levels of competitive development.The objective of this article is to comparatively analyze the components and measurement pillarsof the GCI with the old and new methodology 4.0, as well as the main problematic factors thatweaken and restrict the improvement of the competitive development of Ecuador in the referredperiod. For this, an analytical theoretical methodology was developed, with literature fromsecondary sources to the different reports published from the 2016 to 2019 period of the WEFand other Latin American institutions that collaborate with the calculation of the index and for theanalysis of factors that weaken the level of competitiveness in Ecuador documentary reviewresearch was applied, and websites to public and private institutions. Among the results it standsout that from three components used in the old methodology it was extended to four with the 4.0methodology: Enabling, Human Capital, Market and Innovation Ecosystems, preserving thenumber of 12 competitive measurement pillars. Finally, corruption, bad bureaucracy and stateinefficiency are the main weaknesses that restrict improving competitiveness in Ecuador and atthe regional level.